Islam and professionalism: in search of excellence - Hasan, Md. Mahmudul (OnIslam.net, 2013)
In a world of competition and continuous struggle to achieve progress and prosperity, Muslims need to remind themselves of Islamic work ethics and professionalism. They should go back to the Islamic way of doing things, not necessarily the Muslim way of doing things. They need to go back to the sunnah (tradition) of all Prophets to excel in their work and to establish for them a respectable position in the twenty-first century world. In today’s world, when we think of professionalism or excellence in work, the usual scenario that comes to our mind is, for example, how the Japanese accomplish their work or how people in America and in west European countries perform their professional duties. While we can learn important lessons from the people of these countries, we must appreciate the importance of professionalism in our religion. We should not forget that ‘good work’ and ‘excellence in work’ are two of the most important principles of Islam.